Free radical activity and pro-inflammatory effects of particulate air pollution (PM10) in vivo and in vitro. Issue 12 (December 1996) - Li, X. Y.; Gilmour, P. S.; Donaldson, K.; MacNee, W.
Abstract : BACKGROUND: Epidemiological evidence has implicated fine particulate air pollution, particularly particles less than 10 microns in diameter (PM10), in the development of exacerbations of asthma and chronic obstructive pulmonary disease (COPD) although the mechanism is unknown. The hypothesis that PM10 particles induce oxidant stress, causing inflammation and injury to airway epithelium, was tested. METHODS: The effects of intratracheal instillation of PM10 was assessed in rat lungs (three per group). Inflammatory cell influx was measured by bronchoalveolar lavage (BAL) and air space epithelial permeability was assessed as the total protein in BAL fluid in vivo. The oxidant properties of PM10 particles were determined by their ability to cause damage to plasmid DNA and by changes in reduced (GSH) and oxidised (GSSG) glutathione. The effects of PM10 particles were compared in some experiments with those of fine (CB) and ultrafine (ufCB) carbon black particles. RESULTS: Six hours after intratracheal instillation of PM10 there was an influx of neutrophils (up to 15% of total cells in BAL fluid) into the alveolar space, increased epithelial permeability, the mean (SE) total protein in the BAL fluid increasing from 0.39 (0.01) to 0.62 (0.01) mg/ml, and increased lactate dehydrogenase (LDH) concentrations in the BAL fluid. An even greater inflammatory response was seen following intratracheal instillation of ufCB but not following CB instillation. PM10 particles had free radical activity in vivo, as shown by a decrease in GSH levels in the BAL fluid from 0.36 (0.05) to 0.25 (0.01) nmol/ml following instillation. The free radical activity of PM10 was confirmed in vitro by its ability to deplete supercoiled plasmid DNA, an effect which could be reversed by mannitol, a specific hydroxyl radical scavenger. BAL fluid leucocytes from rats treated with PM10 produced greater amounts of nitric oxide (NO), measured as nitrite (control 3.07 (0.33), treated 4.45 (0.23) microM/1 x 10(6) cells), and tumour necrosis factor alpha (control 21.0 (3.1), treated 179.2 (29.4) units/l x 10(6) cells) in culture than those obtained from control animals. Since the PM10 preparation was contaminated with small amounts of filter fibres due to the extraction process, the effects of instillation of filter fibres alone was assessed. These studies showed that filter fibres did not account for the proinflammatory and injurious effects of the PM10 suspension. CONCLUSIONS: These findings provide evidence that PM10 has free radical activity and causes lung inflammation and epithelial injury. These data support the proposed hypothesis for the mechanism by which particulate air pollution causes adverse effects in patients with airways diseases.